Peace in ancient Egypt - Davies, Vanessa, (Harvard Egyptological studies, 5)
"Around the year 1257 bce, the Egyptian king Ramesses II concluded a treaty with Hattu'ili III, the king of the Hittite empire based in Anatolia. This treaty was not the first that an Egyptian king entered into with another king"--